Conceitos básicos da física dos semicondutores apoiado no uso de software e experimento de baixo custo - Reis, Luana Tavares (2019)
This work aims to insert Semiconductor Physics in the scope of High School (EM). From an educational perspective, the introduction of topics on Modern and Contemporary Physics (FMC) allows the student to perceive that what is studied in the classroom explains the technology contained in his computer, his cell phone, residential alarm systems and others, which shows the transcendence from themes discussed in school to its own experience. Fromthis perspective, the general objective of our research is: to explore the technological development linked to Semiconductor Physics and Electricity, realizing its applicability in the modern world, promoting a student-teacher interaction, research, discussions and group work, based on the theoretical development of significant learningfrom David Ausubel, and therefore improving knowledge and skills in problem solving. Data survey and research applications were performed in a public school in Manaus - AM, located in the North Zone. The application of the educational product followed the steps of a didactic sequence, with the central theme Semiconductor Physics, in which the constructed physical concepts were analyzed with physical and online applications using scratch platform, ending with circuit set up. Student‟s performance analysis was done in parts, class by class, with the intuit of measure positive results on the best way, and at the end of the process the students were able to realize that the contextualization of the themes has great influence on the learning process.From a general point of view, the results obtained were satisfactory, considering the commitment inactivities performed both in classroom or computer and science laboratories, and student‟s evolution in each applied test that was observed mostly as improvement in the written arguments.